Meningkatkan Karakter Peduli Lingkungan Sejak Usia Dini Melalui Kegiatan Green School di PAUD Uswatunn Hasanah Palembang - Lidia Oktamarina (Universitas Bengkulu, 2021)
This study aims to know the process and result of the lesson to improve the environmental care character through the green school. This study is classroom action research which consisted of two cycles. This study used of Kemmis and Taggart’s design which consisted of four stages inevery cycle. The research subjects were 10 students of group B PAUD Uswatuun Hasanah Palembang. The data collection techniques were observation, interview, and documentation. The collected data were analyzed using descriptive qualitative and quantitative methods. The success indicator of this study was if the percentage of environmental care character reached ?71%. The research result shows that the environmental care character after the use of green school increases. Evidenced by an percentage understanding of environmental care character score of 20% pre cycle, then increased in the first cycle of the second cycle of 50% and 80%. Green school can be a solution the increase of the environmental care character from early age.